GE_GERICHTE P/14768/2013 vom 2. März 2015 - GE Cour de justice (2015)
BRIGANDAGE; NE BIS IN IDEM; TORT MORAL; IN DUBIO PRO REO; PRÉSOMPTION D'INNOCENCE | CP.140; CP.47; CP.49.2; CPP.10.3; CPP.11; CO.47